Bisphosphonates: An update - Nalliappan Ganapathy; Subramanium Gokulnathan; Nataraj Balan; Thangadurai Maheswaran; Venkatesan (Wolters Kluwer Medknow Publications, 2012)
Bisphosphonates are used widely for variety of bone condition, most notably IV bisphosphonates in the treatment of metastic bone lesion and oral bisphosphonates for osteoporosis. They constitute a group of drugs capable of modulating bone turnover and reducing its remodeling when an excessive resorption occurs. In the last few years, due to their extensive use, many cases of complications associated with their use have been published. This paper provides recent knowledge on general characteristics of these drugs and their mechanism of action, pathogenesis, as well as their relevance to dentist.